Effect of Self-Etch Primer Application on the Bond Failure Rate of a Mandibular Bonded Lingual Retainer - Ozlu, Fethiye Cakmak; Yazicioglu, Sabahat (BMC, 2022)
BackgroundThe aim of this study was to examine the effect of self-etch primer (SEP) application on the bond failure rate of a mandibular bonded lingual retainer over 24 months. MethodsThe average age of the 86 individuals included in this study was 17 years 4 months. After the removal of the orthodontic appliances, the lingual retainers, which were made of six-stranded stainless steel wire, were bent and bonded onto the lingual surface of all mandibular anterior teeth. The study was performed using a split-mouth design. In the study group, the SEP was administered to the teeth's lingual surfaces. In the control group, they were etched using 37% phosphoric etchant liquid gel. After etching, the primer was applied. The adhesive resin was applied and the retainer was fitted. The patients were re-evaluated over 24 months. The first bond failures and the amount of adhesive remaining on the tooth were recorded as the adhesive remnant index (ARI) scores. The chi-square test was used to compare the bond failure rates (P = 0.231) and ARI scores between the groups (P = 0.162). The survival rates of the retainers were estimated using the Kaplan-Meier test (P = 0.237). The significance level was P < 0.05. ResultsThe bond failure rates, ARI scores, and survival rates did not differ significantly between the groups. ConclusionsThe results of this study demonstrated that an SEP can be used successfully in mandibular lingual retainer bonding. In situations where saliva isolation is difficult, bonding a fixed lingual retainer with SEP is recommended.
Keywords: Bond Failure; Bonded Lingual Retainer; Self-Etch Primer (SEP); Relaps